Azacitidine and lenalidomide combination: a novel relapse prophylaxis regimen after allogeneic hematopoietic stem-cell transplantation in patients with acute myeloid leukemia - Feng, Yimei; Chen, Ting; Zhang, Yun; Yao, Han; Wang, Ping; Wang, Lu; Cassady, Kaniel; Zou, Zhongmin; Liu, Yuqing; Zhao, Lu; Gao, Lei; Zhang, Xi; et al. (Frontiers in Immunology, 2023)
Introduction While allogeneic hematopoietic stem cell transplantation (allo-HSCT) can be a curative regimen for acute myeloid leukemia (AML), relapse of AML remains a serious risk post-transplantation. Once relapsed, salvage options are limited and management of AML is difficult. Here we designed a prospective study to examine the efficacy and tolerability of maintenance therapy with azacytidine (AZA) plus low-dose lenalidomide (LEN) to prevent relapse after allo-HSCT for AML patients (ChiCTR2200061803). Methods AML patients post-allo-HSCT were treated with AZA (75 mg/m2 for 7 days), followed by LEN (5 mg/m2, day 10-28), and a 4-week resting interval, which was defined as one treatment cycle. A total of 8 cycles was recommended. Results 37 patients were enrolled, 25 patients received at least 5 cycles, and 16 patients finished all 8 cycles. With a median follow-up time of 608 (43-1440) days, the estimated 1-year disease free survival (DFS) was 82%, cumulative incidence of relapse (CIR) was 18%, and overall survival (OS) was 100%. Three patients (8%) had grade 1-2 neutropenia without fever; one patient developed grade 3-4 thrombocytopenia and minor subdural hematoma; 4/37 patients (11%) developed chronic GVHD with a score of 1-2, without requiring systemic treatment; No patient developed acute GVHD. After AZA/LEN prophylaxis, increasing numbers of CD56+NK and CD8+ T, and decreasing of CD19+ B cells were observed. Discussion Azacitidine combined with low-dose lenalidomide was observed to be an effective relapse prophylaxis option after allo-HSCT in AML patients, and can be administered safely without significantly increasing the risk of GVHD, infection and other AEs. Clinical Trial Registration www.chictr.org, identifier ChiCTR2200061803.